Hubungan Pengetahuan Ibu dan Status Gizi Balita di Desa Batu Sumur, Manonjaya, Tasikmalaya - Tri Kusuma Agung Puruhita; Anis Abdul Muiz; Yusep Eka Firmasyah (Poltekkes Kemenkes Yogyakarta, 2016)
Background: Nutritional status is a state of the body as a result of the consumption of foods and use nutrients. Diet with the right nutrition and the right then a good nutritional status can be achieved. Factors that can affect nutritional status include the mother’s knowledge, skills, and parenting is done in the family. Objectives: Determine the relationship of maternal knowledge, parenting, and diet andnutritional status of toddler in sub-district Batu Sumur village district Manonjaya Tasikmalaya2014. Method: This study is a survey of a cross-sectional analytic approach. The population is around the 6-60 month-old infants and toddler’s mother in the village of Batu Sumur. Determination of the samples was done by using the simple random about 65 mother and toddler. Data was collectedthrough questionnaires, FFQ, and 24 hour recall sheets, interviews and measurements of weightinfants. Results: Mother’s knowledge included at 53.8%, including parenting are not good at 69.2% andthe diet is not good for 93.8%, while the nutritional status (weight / age) include abnormal of72.3% . Chi-squre test results obtained value of p <0.05 (0.015) showed a significant relationshipbetween parenting style with the nutritional status of toddler, as well as the relationship betweendiet and nutritional status of toddler with p <0.05 (0.005). And not relationship between mother’sknowledge and nutritional status of toddler with p >0.05 (0.581). Conclusion: Parenting and the toddler diet including many who are not good. There is asignificant association between parenting style diet with nutritional status of children, and there isno relationship between knowledge of mothers with nutritional status of children. Keywords: Knowledge, Parenting, Feeding Pattern, Nutritional Status